THE ACTIVITY ANTIMETASTASIS OF ETHANOLIC EXTRACT OF MIRA BILlS JALAPA L. LEAVES AT HUMAN TONGUE CANCER CELL(SP-Cl) - , Shincia Purnamasari ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
The Mirabilisjalapa L is one of plant which has been usedfor medicinein centuries. Its contains Ribosom Inactivating Protein (RIP),saponin, flavonoid, and tannin that can inhibit the growth of cancer cell. The aim this study was to examine the antimetastasis activity of Mirabilis jalapa L etanol extract toward human oral tounge cancer cell supri's clone (SP-Cl). Research design in the study was pure laboratory experimental. This studyused out growth assay method for exanination. SP-Cl wass added at coverglass which has diameter 10 mm.lt was allocated in the middle of petri disk which has diameter 60mm at DMEM with various of etanol extract concentration of Mirabilis jalapa L 0, 7.5, 15, 25, 50, 75 &mu